The effect of traditional and reduced tillage systems on the sediment yield of plots constructed in the Mediterranean climate zone caused by natural rainfall - Yakupoglu, Tugrul; Dindaroglu, Turgay; Akay, Abdullah Emin; Kusvuran, Kadir; Alma, Veysel; Gundogan, Recep (Inderscience Enterprises Ltd, 2020)
The objective of this study was to investigate the effects of different types of tillage systems and different crops on the sediment yield under natural rainfalls from agricultural parcels established in two Mediterranean cities of Turkey. The study was carried out in two consecutive hydrological years, in which both total precipitation and precipitation pattern were different. The results indicated that the soil tillage system (P <= 0.05) and whether or not the plant production was implemented in the parcels (P <= 0.01) had statistically significant effect on the sediment yield of the parcels. Although the total sediment yield was not statistically different for both hydrological years, there was a statistical difference between two years in terms of sediment yield per unit rainfall (P <= 0.01). The applied tillage system and the rainfall pattern are considerably effective on the erosion.
Keywords: fallow; rainfall; sainfoin; sediment; tillage; wheat